Cervicogenic somatosensory tinnitus: An indication for manual therapy? Part 1: Theoretical concept. (June 2016) - Oostendorp, Rob A.B.; Bakker, Iem; Elvers, Hans; Mikolajewska, Emilia; Michiels, Sarah; De Hertogh, Willem; Samwel, Han
Abstract: Tinnitus can be evoked or modulated by input from the somatosensory and somatomotor systems. This means that the loudness or intensity of tinnitus can be changed by sensory or motor stimuli such as muscle contractions, mechanical pressure on myofascial trigger points, transcutaneous electrical stimulation or joint movements. The neural connections and integration of the auditory and somatosensory systems of the upper cervical region and head have been confirmed by many studies. These connections can give rise to a form of tinnitus known as somatosensory tinnitus. To date only a handful of publications have focussed on (cervicogenic) somatosensory tinnitus and manual therapy. Broadening the current understanding of somatosensory tinnitus would represent a first step towards providing therapeutic approaches relevant to manual therapists. Treatment modalities involving the somatosensory systems, and particularly manual therapy, should now be re-assessed in the subgroup of patients with cervicogenic somatosensory tinnitus. The conceptual phase of this study aims to uncover underlying mechanisms linking the auditory and somatosensory systems in relation to subjective tinnitus through (i) review of the literature (part 1) and (ii) through design of a pilot study that will explore characteristics of the study population and identify relevant components and outcomes of manual therapy in patients with cervicogenic somatosensory tinnitus (part 2). This manuscript focusses the theoretical concept of (cervicogenic) somatosensory tinnitus, either with or without secondary central tinnitus or tinnitus sensitization. Highlights: Understanding of neural mechanisms underlying somatosensory tinnitus is the basics for application of manual therapy. Chronic subjective tinnitus combined with secondary central tinnitus is comparable with chronic pain with central sensitization. Manual therapy is a potential treatment in patients with cervicogenic somatosensory tinnitus.